Fundamentals of Bit Selection and Use - Edward L. Johnson; Kylee Jo Duberstein (EDIS)
Choosing an appropriate bit can be a confusing process for horse enthusiasts. This 6-page illustrated fact sheet describes the various types of bits and how to select the best bit for horse and rider. Written by Edward L. Johnson and Kylee J. Duberstein. Published by the UF Department of Animal Sciences, January 2010.